The mark of slavery : disability, race, and gender in antebellum America - Barclay, Jenifer L. (Urbana : University of Illinois Press, 2021)
"Time and again, antebellum Americans justified slavery and white supremacy by linking blackness to disability, defectiveness, and dependency. Jenifer L. Barclay examines the ubiquitous narratives that depicted black people with disabilities as pitiable, monstrous, or comical, narratives used not only to defend slavery but argue against it. As she shows, this relationship between ableism and racism impacted racial identities during the antebellum period and played an overlooked role in shaping American history afterward. Barclay also illuminates the everyday lives of the ten percent of enslaved people who lived with disabilities. Devalued by slaveholders as unsound and therefore worthless, these individuals nonetheless carved out an unusual autonomy. Their roles as caregivers, healers, and keepers of memory made them esteemed within their own communities and celebrated figures in song and folklore. Prescient in its analysis and rich in detail, 'The Mark of Slavery' is a powerful addition to the intertwined histories of disability, slavery, and race"--
Disability, Embodiment, and Slavery in the Old South -- Reimagined Communities: Disability and the Making of Slave Families, Communities, and Culture -- A Dose of Law: The Dialogics of Race and Disability in Southern Slave Law and Medicine -- "Cannibals All!" The Politics of Slavery, Ableism, and White Supremacy -- One Hell of a Metaphor: Disability and Race on the Antebellum Stage.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR platform, viewed February 2, 2022).
eBooks on EBSCOhost
Keywords: Enslaved persons -- Abuse of -- United States -- History -- 19th century; African Americans with disabilities -- History -- 19th century; People with disabilities -- Abuse of -- United States -- History -- 19th century; People with disabilities -- United States -- Social conditions -- History -- 19th century; Enslaved persons -- United States -- Social conditions -- 19th century; United States -- Race relations -- History -- 19th century; Esclaves -- Violence envers -- États-Unis -- Histoire -- 19e siècle.; Noirs américains handicapés -- Histoire -- 19e siècle.; Personnes handicapées -- États-Unis -- Conditions sociales -- Histoire -- 19e siècle.; Esclaves -- États-Unis -- Conditions sociales -- 19e siècle.; États-Unis -- Relations raciales -- Histoire -- 19e siècle.; Personnes handicapées -- Exploitation financière -- États-Unis -- Histoire -- 19e siècle.; SOCIAL SCIENCE / General; African Americans with disabilities; People with disabilities -- Abuse of; People with disabilities -- Social conditions; Race relations; Enslaved persons -- Abuse of; Enslaved persons -- Social conditions; United States; 1800-1899; History